Pendekatan Multilevel Sebagai Upaya Meningkatkan Pemberian ASI Eksklusif - Nur Khamidah; Yayi Suryo Prabandari; Detty Siti Nurdiati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2021)
Increasing exclusive breastfeeding effort was continued in Jember district. Local government collaborates with USAID to increase breastfeeding promotion program. Health promotion program used multilevel approach. This study aimed to evaluate exclusive breastfeeding program and impact program to increasing breastfeeding in Jember district. This study method used cross sectional study in two population with mix method approach (qualitative and quantitative). Collecting qualitative data was using participative observation, indepth interview and focus group discussion to describing program. Collecting quantitative data was using questionare to evaluate impact program in two populations (120 respondent program and 125 respondent non program). Data was analyzed by open code in qualitative data. To analyzed quantitative data was used chi square.  The research result shows that Health promotion program increased exclusive breastfeeding was using multilevel approach. In top level, implementation of the program was regulation government policy number 17, 2013 about save childbirth, initiation breastfeeding and exclusive breastfeeding. In the middle level implementing program by Jember health department and local government clinic through peer breastfeeding support, mother pregnant class and promote by midwife. Lower level evaluation result was that two population program and non program have different significant. Population who give program have 2,4 higher OR value in exclusive breastfeeding than population not give the program. Based on this research it can be concluded that multilevel approach can used to increasing exclusive breastfeeding until six month. Government support was needed to successful program.